A COMPARATIVE PHYTOCHEMICAL ANALYSIS OF GENUINE AND MARKET SAMPLE OF GAJAPIPPALI W.S.R TO SCINDAPSUS OFFICINALIS SCHOTT (ARACEAE) - Nigamanand, Bal; Suresh, Chaubey; Chandra, Tiwari Ramesh; Bardhan, Naithani Harsh (International Journal of Ayurveda and Pharma Research, 2016)
Gajapippali (Scindapsus officinalis Schott.) is one of the plants used in Indian system of medicine belongs to family Aracea. In the present study physicochemical analysis and preliminary phytochemical screening of fruits of genuine and market sample have been carried out. The total ash is found to be 9.67%, 6.74%, 6.6%, the acid insoluble ash is found to be 1.12%, 0.57%, 0.7%, the water soluble ash is found to be 16.75%, 19.59%, 19.6% respectively both in genuine and market sample. The alcohol soluble extractive value is found to be 11.53%, 9.56%, 9.6%, the aqueous soluble extractive value is found to be 19.65%, 18.91%, 18.94%, the petroleum-ether extractive value is found to be 4.59%, 3.65%, 3.7% respectively both in genuine and market sample. The moisture content is found to be 6.4%, 3.6%, 3.5% respectively both in genuine and market sample. The pH value is found to be 8.1, 6.8, 6.8 respectively both in genuine and market sample. Preliminary phytochemical screening of successive extracts of fruit reveals the presence of various secondary metabolites such as Alkaloids, glycosides, saponins, tannins, steroids, phenolic compounds, amino acids, proteins and carbohydrates. The TLC and HPTLC finger print study also carried out in both genuine and market sample. By the study I have sure that this work will be helpful to further standardization of the drug.